Prediksi Erosi Dan Arahan Penggunaan Lahan Di Bagian Hulu Das Wai Illa Desa Amahusu Kecamatan Nusaniwe Kota Ambon - Rudy Soplanit; Junet Putinella; Elga Siwalette Siwalette (Faculty of Agriculture, Pattimura University, 2016)
The use of land without a good management lead to land destruction and environmental damage. Prevention should be done by soil conservation. The objective of this research was to estimate the level of soil erosion in the upstream of watershed area of Wai Illa by using a survey method for field observations and USLE (Universal Soil Loos Equation) method to predict the amount of eroded soil. The results showed that the existing land use in areas of research was mixed farms, and scrub with a low level of soil damage on land L433 unit1 and high slopes on the land slopes L533 unit 4. It was predicted that actual annual erosion ranged from 16.524 t/ha up to 315.659 t/ha.